Heavy Metals Pollution of Storm Sewer Sediments in Xicheng District, Beijing, China - Li, Haiyan; Mei, Huirui; Xu, Boping; Wang, Chongchen (Asian Journal of Chemistry, 2011)
Total organic carbon (TOC) and heavy metal content, like Cr, Cu, Zn, Cd, Pb and Ni, in the sediment samples taken from 6 different locations in Xicheng District, Beijing, were analyzed. The chemical forms of the metals in the sediment samples were determined after five-steps sequential extraction. The results reveal that the sediments in the storm sewer contain high concentration of total organic carbon and heavy metals. The values of total organic carbon range from 23.39-58.17 mg/g, with mean value of 50.64 mg/g. The mean concentrations of Cr, Cu, Zn, Cd, Pb and Ni are 78.84, 137.92, 590.08, 0.474, 44.67 and 43.61 mg/kg, respectively. The contamination level and ecological risk were assessed using geo-accumulation index (Igeo) and potential ecological risk indexes (RI), respectively. A negative conclusion can be drawn that the sediments in the storm sewers located in Xicheng district, Beijing, China contain high content of some heavy metals, which can lead to high potential ecological risk to receiving water bodies with the help of rainwater runoff.